Produção de biomoléculas por fermentação de glicerol utilizando micro-organismos isolados de rúmen bovino - Damasceno Junior, Clério Valentin (2012)
Seeking for cleaner energy sources Brazil established in 2005 in the law n° 11097 that stipulates the addition of biodiesel to diesel sold at gas stations, making the biofuel production increase exponentially. In addition to the biodiesel production is generated de amount of 10% glycerol during the process, which is already becoming problematic for manufacturers and can become an environmental liability. Biotechnology can be used to transform glycerol into biomolecules with higher value remedying the problem and to increase the profitability of production of biodiesel. This paper aims to isolate a microorganism, observe and quantify the degradation of glycerol and the products of their metabolism. Using the bovine rumen as a source of microorganisms, it was possible to isolated and identify using techniques of biochemical tests, the glycerol degrading bacteria, Klebsiella pneumoniae. The bacteria was grown in culture media containing glycerol as the sole carbon source, one containing glycerol P.A. added sodium thioglycollate, another containing glycerin from the biodiesel production added sodium thioglycollate and a third with only glycerin without the addition of sodium thioglycollate. The fermentation were conducted in erlenmeyers for 120 h at 37 °C where samples were taken, aseptically, every 24 hours and they were filtered, centrifuged and analyzed with the method of high performance liquid chromatography. In the media where there P.A. glycerin was added at the end of the process the production of 12,53 g/L of 1,3-propanediol (20.76 % conversion) and 1,50 g/L of ethanol (2 % conversion), the media containing glycerin and sodium thioglycollate production was 22.53 g/L of 1,3-propanodiol (27,44 % conversion), 1,42 g/L of ethanol (1,73 % conversion) and 1,13 g/L of 2, 3-butanediol (1,37 % conversion), in the media containing glycerin without the addition of sodium thioglycolate was 29,41 g/L of 1,3-propanediol (30,06 % conversion), 1.03 g/L of ethanol (1,31 % conversion) and 2,32 g/L of 2,3-butanediol (2,76% conversion). The Bacteria isolated and identified was Klebsiella pneumoniae. The media containing only glycerin was the most efficient in the conversion of glycerol to 1,3-propanediol and 2,3-butanediol and the glycerin P.A. with media containing sodium thioglycollate was more efficient in conversion of glycerol to ethanol.